(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
In some of the “prayers for justice” found in Britannia and Pannonia Superior, a period of nine days regarding the punishment of the thief by the god or goddess is mentioned. This paper aims to elucidate whether this allusion is due to the influence of the ancient Roman nundina or, alternatively, could be expressing a time unit charachteristic of the Celts on the ground of the evidence in the literary texts from Ireland and Wales as well as in the Gaulish calendar of Coligny (Ain).